A PROPOSED SCIENCE PROGRAM FOR GENERAL EDUCATION AT CASTLETON TEACHERS COLLEGE, CASTLETON, VERMONT. - Sleeman, Richard Alexander (Science Education, 1961)
The study aims to determine what science program should be offered for general education at Castleton Teachers College in Castleton, Vermont. The proposed science program was based upon the problem approach. This means that the teaching approach is centered on the identification, clarification, analysis and solutions of problems by teachers and students. The underlying assumption for using the problem approach in this science program is that the students will teach better if they have grappled with the common problems of people living the society, acquainted with the issues about which present knowledge is inadequate and have organized their own thinking and attitudes. This program is an experience-centered program, it provides for real and meaningful experiences in the physical, biological and social environment.